An Analysis of Machine Learning Solution for QoS and QoE in Network (Infrastructure Oriented and Less) - Kanimozhi, N; Hari Ganesh, S; Karthikeyan, B (International Journal of Computer Sciences and Engineering, 2023)
Now, Communication network (Network may be a wired or wireless network. In wireless network it may be an infrastructure oriented or infrastructure less) plays vital role in the world. . At present without network people cannot do their work easily. Communication Network described as two or more device connecting together and share its resources. If a resource is accessed by more than one person. Network faces lot of issues in its Qualitative and Quantitative of Service. This paper is try to provide solution for infrastructure oriented and less network QoS (Quality of Service) and QoE (Quality of Experience) problems using AI and ML.